Formulasi Mecaf Cookies Berbasis Tepung Mocaf dan Kacang Merah Sebagai Alternatif Snack Penderita Diabetes Melitus - Dwitantika, Bryan; Priawantiputri, Witri; Rahmat, Mamat; Sulaeman, Agus (Jurusan Gizi Poltekkes Kemenkes Bandung, 2025)
According to the 2018 Basic Health Research (Riskesdas), the prevalence of diabetes mellitus in Indonesia reached 1,017,290 people, increasing from 6.9% to 8.5%. Individuals with diabetes mellitus benefit from having a regular eating schedule, which helps synchronize the body’s insulin response. Snacks is important role in preventing drops in blood sugar levels. Cookies can be a suitable snack alternative. This research utilized local food ingredients, namely mocaf flour and red bean flour. The study aimed to determine the effect of mocaf flour and red bean flour formulation on the quality of